BaySeddo connecting Senegalese farmers to crowsourced investor funds - Sall, Mamadou (Technical Centre for Agricultural and Rural Cooperation, 2019)
Mamadou Sall, Co-Founder of BaySeddo 2.0 (Senegal) shares how his initiative is connecting farmers to have land but no finance to investors who are interested in agriculture.